Sustainable development 'outside' the European Union: What role for impact assessment? - Camilla Adelle; Julia Hertin; Andrew Jordan (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2005)
Sustainable development is a cross-cutting issue par excellence that necessitates a very high degree of policy coordination. This is especially true considering that the European Union's 2001 Sustainable Development Strategy demands that all European Union (EU) policies actively support the sustainable development of other countries, particularly those in the developing world. In order to fulfil this ambitious obligation, the EU has pledged to consider the impacts that all new policies have within and outside the EU as part of a new Impact Assessment (IA) regime. This paper aims to evaluate how well the new IA regime has helped address the 'external' dimensions of sustainability through the analysis of potential effects of EU policies on non-EU countries. It finds that the IA procedure does not currently function as an effective instrument for the implementation of the Union's commitment to promoting sustainability in the developing world. Other coordination mechanisms need to be considered given the horizontal and vertical complexity of this challenge.
Keywords: 330; developing countries; European Union; impact assessment; networks; policy coordination; Sustainable Development